The emerging role of systems biology for engineering protein production in CHO cells. (June 2018) - Kuo, Chih-Chung; Chiang, Austin WT; Shamie, Isaac; Samoudi, Mojtaba; Gutierrez, Jahir M; Lewis, Nathan E
Graphical abstract: Highlights: 3 waves of innovation have enhanced protein production in CHO cells. Systems-level methods are now unravelling drivers of protein production. Predictive models will facilitate rational cell engineering for protein production. Abstract : To meet the ever-growing demand for effective, safe, and affordable protein therapeutics, decades of intense efforts have aimed to maximize the quantity and quality of recombinant proteins produced in CHO cells. Bioprocessing innovations and cell engineering efforts have improved product titer; however, uncharacterized cellular processes and gene regulatory mechanisms still hinder cell growth, specific productivity, and protein quality. Herein, we summarize recent advances in systems biology and data-driven approaches aiming to unravel how molecular pathways, cellular processes, and extrinsic factors (e.g. media supplementation) influence recombinant protein production. In particular, as the available omics data for CHO cells continue to grow, predictive models and screens will be increasingly used to unravel the biological drivers of protein production, which can be used with emerging genome editing technologies to rationally engineer cells to further control the quantity, quality and affordability of many biologic drugs.